The First Year of Acculturation: A Longitudinal Study on Acculturative Stress and Adjustment Among First-Year International College Students - Koo, Katie; Baker, Ian; Yoon, Jiyoon (Journal of International Students, 2021)
We analyzed 192 first-year international college students in the Mid-Atlantic region to examine the change in international students’ acculturative stress, adjustment, and collegiate experiences during their first year of enrollment in U.S. higher education. We found that male students, students from low socioeconomic status backgrounds, and students majoring in the humanities showed higher rates of acculturative stress and lower rates of satisfaction with college experiences compared with their counterparts. International students reported decreased acculturative stress and homesickness and increased English proficiency, social connectedness, and satisfaction with college experiences during the last week of the first year compared to the first week of their first semester. Satisfaction with college experiences, English proficiency, social connectedness, and self-esteem were significant predictors of acculturative stress. Lastly, acculturative stress at the beginning of the first year and satisfaction with college experiences at the end of the first year affected each other reciprocally over 1 year.